2015
DOI: 10.7812/tpp/14-188
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Multinational Association for Supportive Care in Cancer (MASCC) Risk Index Score as a Criterion for Nonadmission in Febrile Neutropenic Patients with Solid Tumors

Abstract: Febrile neutropenic episodes in patients with solid tumors were identified electronically from 10/1/2008 to 11/15/2010. Inclusion criteria were met in 198 episodes. Sensitivity, specificity, and positive and negative predictive values of the MASCC risk index score vs complications were, respectively, 94%, 29.6%, 57.7%, and 82.9%. An MASCC risk index score of 21 or greater could not be used as a criterion for "no complication/ do not admit." Inability to eat should be an admission criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…Moreover, a few studies demonstrated similar results: the complementary relationship between the MASCC RIS and CISNE. [12, 15, 16] The MASCC RIS seems to be suitable for ‘at a glance’ screening—that is, only a few elements ED physicians can quickly identify are sufficient for the triage. The physicians may hospitalize the patients at high risk whatever criteria they refer to, MASCC high risk or CUP, as proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a few studies demonstrated similar results: the complementary relationship between the MASCC RIS and CISNE. [12, 15, 16] The MASCC RIS seems to be suitable for ‘at a glance’ screening—that is, only a few elements ED physicians can quickly identify are sufficient for the triage. The physicians may hospitalize the patients at high risk whatever criteria they refer to, MASCC high risk or CUP, as proposed.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Studies have shown an increased likelihood of febrile neutropenia in humans treated with chemotherapy for patients who are elderly, ≤2 m 2 , have a poor performance status, have haematopoietic tumours and have received extensive pretreatment with other chemotherapeutic agents. [12][13][14][15][16] An increased risk of febrile neutropenia from chemotherapy has also been reported for dogs with lower body weights. 17 While neutropenia is considered an adverse effect of chemotherapy, previous studies in dogs with lymphoma treated with a multidrug chemotherapy protocol have suggested that chemotherapy-induced neutropenia resulted in prolonged remission and survival times.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 10 ] However, this score was not designed to detect bacteremia, and is insufficiently accurate even for its intended use, prediction of safe discharge, with a negative predictive value for complications of only 83%. [ 11 ] Consequently, many clinicians do not rely on it, admitting all FN patients by default. [ 5 , 6 ] A newer score, the Clinical Index of Stable Febrile Neutropenia, is also inadequate, with a 9.1% rate of bacteremia in the low-risk group.…”
Section: Introductionmentioning
confidence: 99%